Ocimum sanctum leaf extract induces drought stress tolerance in rice. (3rd May 2016) - Pandey, Veena; Ansari, M.W.; Tula, Suresh; Sahoo, R.K.; Bains, Gurdeep; Kumar, J.; Tuteja, Narendra; Shukla, Alok
ABSTRACT: Ocimum leaves are highly enriched in antioxidant components. Thus, its leaf extract, if applied in plants, is believed to efficiently scavenge ROS, thereby preventing oxidative damage under drought stress. Thus, the present study was performed in kharif 2013 and rabi 2014 season to evaluate the effect of aqueous leaf extract of Ocimum sanctum against drought stress in 2 rice genotype under glass house conditions. Here we show that various morpho- physiological (chlorophyll fluorescence, leaf rolling score, leaf tip burn, number of senesced leaves and total dry matter) and biochemical parameters (proline, malondialdehyde and superoxide dismutase content) were amended by Ocimum treatment in both the seasons. Application of Ocimum extract increased expression of dehydrin genes, while reducing expression of aquaporin genes in drought stressed rice plant. Thus, application of Ocimum leaf extract under drought stress can be suggested as a promising strategy to mitigate drought stress in economical, accessible and ecofriendly manner.